Semiotic and Implication of Hijab toward Da’wah in Indonesia - Nur Kumala (UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
Subjectivity of meaning can’t be separated from human, for example the case of hijab. This research used quantitative method with semiotic approach. It also used Roland Barthes' semiotics with his 3 buildings (denotative, connotative and myth debunking) of QS. Al-Ahzab: 59, and connotative activities that dissolve in social practices in society. The results of this research indicated that the existence of the use of the headscarf and the leaning of the meaning of the headscarf as a standardization of women's religiosity was a myth, and become an ideology when it justified the meaning and blames other meanings. The meaning of shalihah women is women who wears hijab, or the longer the veil, the more shalihah she is. It is contrary to the goal of Islam as the basis for da'wah that always puts forward goodness and avoids badness (jalbul mashalih-dar'ul mafasid); do not force and preach well (amar ma'ruf nahy munkar bil ma'ruf).